The Eco 6 / Eusoff Noor Azizan Rahman ... [et al.] - Rahman, Eusoff Noor Azizan; Arifin, Muhamad Iqbal; Zamzaimi, Nur Zaitul Aqma; Jamaludin, Nazrul Helmy (2024)
In our project, our task was to create furniture that's not only comfortable but also eco-friendly. To achieve this, we incorporated sustainable and functional design elements. One such example is our multi-use chair, which serves both practical and versatile purposes. Additionally, we integrated features like recycle bins and used wood-plastic composite material to reduce environmental impact. Moreover, we included a donation box to encourage recycling and charitable acts. In terms of design, we emphasized repetition and symmetry to enhance visual appeal and functionality. Our primary goal was to produce furniture that's cozy, stylish, and suitable for everyone, particularly the students of UiTM Seri Iskandar, Perak. By combining comfort, sustainability, and functionality, we aimed to create pieces that cater to various needs while minimizing our ecological footprint. Our commitment to eco-friendly practices extends beyond material choice, including features that promote recycling and charitable giving. Ultimately, our furniture reflects our dedication to crafting items that not only provide comfort but also contribute positively to the environment and society. We believe that by prioritizing sustainability and thoughtful design, we can create spaces that enhance both comfort and well-being for all users.